Sub-segmental pulmonary emboli as a marker of CT-pulmonary angiogram overuse in a single-center retrospective cohort study: A dimer a dozen?. Issue 196 (December 2020) - Gerstein, Lindsey; Koolian, Maral; Schwartz, Blair C.
Highlights: Overuse of CT pulmonary angiography is a burden on patients & the healthcare system. Sub-segmental pulmonary emboli (SSPE) can be considered a marker of overuse. No risk prediction tools exist in inpatients to guide pulmonary embolism diagnosis. We found a higher incidence of SSPE, and thus increased overuse, in inpatients. There is a need to develop & validate clinical prediction tools for inpatients.